Interactive Illustrated Reading Box Media for Primary School Character Education: Media Kotak Bacaan Bergambar Interaktif untuk Pendidikan Karakter di Sekolah Dasar - FERI TIRTONI; Richmatul Jannah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Education plays an indispensable role in national progress by cultivating independent, educated, and ethical citizens. Specific Background In the Indonesian primary education context, early cultivation of civic values through physical instructional media is essential to build strong character traits like mutual cooperation and tolerance. Knowledge Gap However, conventional teaching methods often struggle to address current moral crises due to a lack of highly engaging visual tools that seamlessly integrate physical elements with digital assets. Aims This study designs an interactive visual learning tool named Smart Box to improve student understanding of national principles. Results The developed square-shaped visual medium features four functional sides incorporating storytelling, matching stickers, and dice games, while successfully integrating quick-response barcodes for digital ice-breaking videos and daily application lessons. Novelty The unique value of this media lies in its multi-sided, handmade physical architecture combined with mobile-scannable digital links that prompt active physical participation. Implications This innovative approach offers an actionable solution for educators to deliver moral education dynamically, transforming passive learning into an immersive classroom experience. Keywords: Character Education, Learning Media, Primary School, Smartbox, Visual Tools Key Findings Highlights The multi-sided physical media successfully engages students through interactive games, storytelling, and tactile sticker-matching activities. Quick-response barcode integration seamlessly bridges physical classroom tools with digital video lessons and dynamic ice-breaking exercises. The handmade four-layered layout provides a structured, highly visual framework for delivering moral and national value systems.